Too old for this, too young for that! : your survival guide for the middle school years - Mosatche, Harriet S., 1949-; Unger, Karen, 1954- (Minneapolis, MN : Free Spirit Pub., 2010)
Provides information, advice, quizzes, and activities aimed at helping middle school students deal with physical and emotional changes, relationships, peer pressure, and other challenges.
Includes index.
7.4
5-8.
5-8
Keywords: Adolescent psychology -- Juvenile literature; Middle school students -- Life skills guides -- Juvenile literature; Middle school students -- Psychology -- Juvenile literature; Preteens -- Life skills guides -- Juvenile literature; Preteens -- Psychology -- Juvenile literature; Teenagers -- Life skills guides -- Juvenile literature; Adolescent psychology; Middle school students -- Life skills guides; Middle school students -- Psychology; Preteens -- Life skills guides; Preteens -- Psychology; Teenagers -- Life skills guides; Adolescent psychology; Middle school students -- Life skills guides; Middle school students -- Psychology; Preteens -- Life skills guides; Preteens -- Psychology; Teenagers -- Life skills guides